CLASS MANAGEMENT IN LEARNING - Nada Fristy Yusri; Neviyarni; Herman Nirwana (Literasi Nusantara, 2021)
The teacher's role is very important in the creation of successful learning and the achievement of learning objectives. In the classroom, teachers not only teach but also have skills in classroom management. Classroom management is the duty and responsibility of a teacher in the classroom. Classroom management is useful for creating and maintaining an atmosphere and conditions in the class and restoring class conditions to be optimal. The intended condition is a comfortable, safe, and pleasant condition that is felt by students and teachers. Classroom management which emphasizes on how to manage existing individuals will be more helpful and support personal development, both personally for students and personal teachers. Classes that are managed in this way, students will not only develop intellectually, but also affective, conative, and social aspects.